The Encyclopedia of Strikes in American History. - Brenner, Aaron (Taylor and Francis, 2015)
Strikes have been part of American labor relations from colonial days to the present, reflecting the widespread class conflict that has run throughout the nation's history. Against employers and their goons, against the police, the National Guard, local, state, and national officials, against racist vigilantes, against their union leaders, and against each other, American workers have walked off the job for higher wages, better benefits, bargaining rights, legislation, job control, and just plain dignity. At times, their actions have motivated groundbreaking legislation, defining new rights fo.